Autoimmune necrotising myopathy and HMGCR antibodies. Issue 2 (8th February 2018) - Karunaratne, Kushan; Amiras, Dimitri; Pickering, Matthew C; Hofer, Monika; Viegas, Stuart
Abstract : Statins lower serum cholesterol concentrations by inhibiting the enzyme 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR). Muscle side effects are relatively common and include asymptomatic elevation of serum creatine kinase (CK), myalgia, proximal muscle weakness and rhabdomyolysis. More recently, a subset of cases of immune-mediated necrotising myopathy has been found to have antibodies against HMGCR. It is often an aggressive and debilitating myopathy and has a complex pathogenesis characterised by fibre necrosis, usually with minimal associated inflammation. Not all such patients are taking statins. The general consensus is that best treatment involves withdrawing the statin and giving immunosuppressive and immunomodulatory treatment. We describe three cases of HMGCR-related immune-mediated necrotising myopathy, detailing their clinical course and subsequent management, illustrating the spectrum of this disorder.